Dapatkah Love of Money Memoderasi Pengaruh Literasi Keuangan terhadap Online Shop Performance? - Maulidyaningtiyas, Maulidyaningtiyas; Hidayat, Rendra Arief (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This research aimed to test and analyze the influence of financial knowledge, attitude, and behavior on online shop performance with love of money as moderator. Quantitative descriptive was used as research methode and primer data was obtained by distributing surveys to 100 young entrepreneurs in East Java. Research data was analysed using multiple and moderated regression analysis through IBM SPSS Statistics 26 application. The result show the influence of financial knowledge, attitude, and behavior on the online shop performance simultaneously however, only financial behavior that show a significant influence and thus love of money is only able to moderate the influence of financial behavior on the online shop performance. These results emphasize the importance of financial literacy and various parties support regarding increasing financial literacy through financial education or training for young entrepreneurs.